Generational Perspectives on Fintech Adoption: Challenges, Demographics, and Digital Inclusion - Singh, Avtar (Mercados y Negocios, 2025)
This research aims to examine how different generations in India adopt fintech services, considering the main barriers and demographic factors that influence these patterns. Based on a survey of 278 banking customers in Punjab and Jammu and Kashmir, it is evident that Generation Z and millennials have embraced fintech services more than Generation X, with key obstacles including a lack of technical skills, concerns about cybersecurity, and strict regulations. The findings suggest that implementing measures tailored to each generation will be essential in promoting digital financial services and bridging the gap between those who can access these services and those who cannot. Although fintech companies are increasingly recognised in the payments industry, the primary challenges to the rapid growth of the fintech ecosystem in India include "lack of technical know-how," "low security (fraud messages, calls, etc.)," regulatory and compliance laws, "documentation and formalities," and "emotional attachment to cash." Governments, financial institutions, regulators, and Indian fintech firms must collaborate to address these structural issues from the ground up, expand their reach, enhance consumer satisfaction, and make digital channels more accessible.